PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN KONFLIK INTERPERSONAL SISWA KELAS X MIA 1 SMAN 1 PEKANBARU - Rizalil fiqri; Rosmawati '; Tri umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The title of this research is the Effect of group counseling services to the consult to decrease interpersonal conflict . Objective: This study aimed to determine the effect of Guidance Services consult to Interpersonal Conflict Students SMAN 1 Pekanbaru . This type of research used in this study is the real- experimental with patterns pretest – posttest control group design . The subjects were students of class x mia 1 which has a hight Interpersonal Conflict in SMAN 1 Pekanbaru . From the results of the Spearman correlation coefficient test results obtained through SPSS Sig .( 2– tailed) = 0.043 Sig value .( 2– tailed) < 0.05 ( 0.043< 0.05), it can be concluded that there is a significant relationship between group guidance on Interpersonal Conflict.Keywords : Guidance group , Interpersonal Conflict